Resource-use strategies of woody plants in grassy ecosystems - Wedel, Emily R. (Kansas State University, 2024)
Grasslands and savannas contain diverse assemblages of herbaceous and woody species that contribute to ecosystem processes and maintenance of vegetation diversity and structural heterogeneity. The balance between these co-existing functional groups is maintained by fire, herbivory, and rainfall distribution. Woody species in grasslands and savannas are structurally and physiologically diverse and use a variety of strategies to establish and survive in these high-disturbance ecosystems. These strategies include deep root systems to mitigate drought stress, high belowground carbohydrate storage to resprout after disturbance, and dense canopies to shade out highly competitive grasses. Changes in climate and land management over the last century have favored woody plants and led to the rapid expansion of woody species into grassy ecosystems across the world in a process known as woody encroachment. In this dissertation, I used a broad suite of studies to assess the strategies used by trees and shrubs to grow and persist in lowveld savanna (Limpopo province, South Africa) and tallgrass prairie (eastern KS, USA). In the first half of my dissertation, I used an in situ irrigation manipulation experiment in northeastern South Africa to (1) assess how the intensity, frequency, and timing of irrigation impacts the growth of six common savanna tree species (Chapter 2) and (2) understand how variation in water availability affects belowground processes such as root productivity and water partitioning among savanna trees and grasses (Chapter 3). Irrigation was used to manipulate the frequency, magnitude, depth, and timing of soil water availability for savanna tree saplings and co-existing grasses. I found few differences in above and belowground tree growth in response to variation in irrigation, but interspecific differences in tree growth reflected their leaf physiology and tree saplings used deeper soil water than grasses. Our results suggest that an increase in water availability benefits tree growth regardless of the frequency or intensity of rainfall and root niche separation between trees and grasses occurs early in sapling establishment. In the second half of my dissertation, I focused directly on the expansion of woody plants in grassy ecosystems. First, I explored the impacts of repeated shrub removal on community responses and shrub physiology in lowveld savanna (Chapter 4). Stems of the dominant woody species, Colophospermum mopane, were repeatedly cleared for 7 years in a semi-arid savanna. I found that 6-7 years of repeated clearing was necessary to induce large-scale shrub mortality. In addition, areas with reduced shrub cover had increased soil water availability, greater grass biomass, and attracted more herbivores compared to areas that were not cleared, suggesting dense woody vegetation reduces herbaceous biomass and alters ecosystem hydrology in this system. In my last study, I characterized the physiological traits and growth strategies of the most abundant woody encroaching species in tallgrass prairie (Chapter 5). I found that encroaching species encompass a spectrum of growth forms and leaf physiology, and two of the most abundant species fell at opposite ends of this spectrum. These results suggest niche complementarity promotes the encroachment of several woody species in tallgrass prairie. Together, my work highlights the diverse strategies used by woody plants to establish and persist in disturbance-prone grassy systems and the mechanisms that underlie the encroachment of the most abundant woody species.
Keywords: Savanna; Plant physiology; Woody encroachment; Rainfall variability; EcologyGrassland